Kritik Implentasi Corporate Social Responsibility Pada Perusahaan Minyak Dan Gas Perspektif Maqasid Al-Syari’ah - Joko Hadi Purnomo; Moh. Agus Sifa' (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2020)
Corporate Social Responsibility is an interesting topic, since various theories are used as a basis for implementing it. Oil and Gas Company is one of the entities that practice Corporate Social Responsibility. The Corporate Social Responsibility implementation in oil and gas companies is oriented to their own interests in achieving the optimal profits. Oil and gas as one of the natural resources included in community ownership cannot be owned absolutely by anyone, including individuals, groups and even countries. The method used was a critical review of the Corporate Social Responsibility implementation in oil and gas companies. The results showed that the Corporate Social Responsibility implementation of oil and gas companies referred to the theory of shareholders oriented to the interests of shareholders. Corporate Social Responsibility implementation was only used to build a company’s reputation, so that the company would get increasing profits. The Corporate Social Responsibility implementation of oil and gas companies which referred to the theory of stakeholders was only oriented towards building public confidence that the company was sincere in carrying out Corporate Social Responsibility projects, but basically its expectations were on the company’s reputation. In addition, the involvement of stakeholders was not given room to make decisions about Corporate Social Responsibility implementation. Corporate Social Responsibility in the perspective of maqasid al-syari’ah must fulfill 4 (four) main components, consisting of maqasid al-syari’ah compliance, formation of a multi-stakeholder body, establishment of a Sharia Board, and fulfillment of sharia compliance. Keywords: Corporate Social Responsibility, Oil and Gas Companies, Maqasid Al-Syari’ah